Examining School and Madrasah Education Policies in Post-Pandemic Learning Recovery in Indonesia - Asy'arie, Bima Fandi; Permata Sari, Putri; Mariyana, Weni; Aly Mustofa, Moh. (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2024)
This research is to identify and analyze how education policies in Indonesia can be further improved after the Covid-19 pandemic in schools and madrasas. This article focuses on data (Kemendikbudristek), with a focus on the post-pandemic learning recovery agenda. This research is library research, with a qualitative approach. Data was obtained from three sources “Google Scholar”, “ScienceDirect”, and “DOAJ”. The discussion in this article highlights that learning applications must be compatible with 21st century skills. Then it is important to build commitment to mastering basic literacy and numeracy skills. The Ministry of Education and Culture's (Kemendikbudristek) agenda in responding to the recovery of learning after the pandemic is: First, presenting the National Assessment (AN) as a substitute for the National Examination (UN) which focuses on the development and improvement of learning outcomes as well as the school and madrasah environment. Second, the development of digital technology in learning activities. Where, technology certainly cannot replace the role of teachers as the spearhead of education. Third, it is important to renew the world's commitment to education in the education transformation conference. “Transforming Education Summit” (TES). Fourth, reorganize education and accelerate educational progress and the 2030 SDGs agenda. Apart from that, Nadiem’s statement explained that mutual cooperation is the basis for the transformation of Indonesian education, especially in post-pandemic learning recovery, because this form of mutual cooperation is the key to transformation to create higher quality education, that will bring a better and more sustainable future.